Hiatal hernia on thoracic computed tomography in pulmonary fibrosis. Issue 3 (12th May 2016) - Tossier, Céline; Dupin, Clairelyne; Plantier, Laurent; Leger, Julie; Flament, Thomas; Favelle, Olivier; Lecomte, Thierry; Diot, Patrice; Marchand-Adam, Sylvain
Gastro-oesophageal reflux has long been suspected of implication in the genesis and progression of idiopathic pulmonary fibrosis (IPF). We hypothesised that hiatal hernia may be more frequent in IPF than in other interstitial lung disease (ILD), and that hiatal hernia may be associated with more severe clinical characteristics in IPF. We retrospectively compared the prevalence of hiatal hernia on computed tomographic (CT) scans in 79 patients with IPF and 103 patients with other ILD (17 scleroderma, 54 other connective tissue diseases and 32 chronic hypersensitivity pneumonitis). In the IPF group, we compared the clinical, biological, functional, CT scan characteristics and mortality of patients with hiatal hernia (n=42) and without hiatal hernia (n=37). The prevalence of hiatal hernia on CT scan at IPF diagnosis was 53%, similar to ILD associated with scleroderma, but significantly higher than in the two other ILD groups. The size of the hiatal hernia was not linked to either fibrosis CT scan scores, or reduction in lung function in any group. Mortality from respiratory causes was significantly higher among IPF patients with hiatal hernia than among those without hiatal hernia (p=0.009). Hiatal hernia might have a specific role in IPF genesis, possibly due to pathological gastro-oesophageal reflux. Hiatal hernia in idiopathic pulmonary fibrosis was associated with mortality from respiratory causes http://ow.ly/